PERANCANGAN DESAIN UI/UX APLIKASI MOBILE EXPLORER.ID - Karunia, Vira Anisa; Juanda, Edwar (Anggada : Jurnal Desain dan Seni, 2021)
Explorer.ID mobile application is one of travel applications that provide open trip tours to many points of interests in various parts of Indonesia. With mobile application made available, Explorer.ID is hoping to expand its target consumers as well as implementing sustainable tourism concept to its trip packages along the way. After the author observes users’ habit while using Explorer.ID mobile application, there are many peculiarities within the mobile application that has left users confused. Some of the peculiarities is that; One, there’s not enough information provided regarding the payment methods. Two, how there’s no feature that enable users to control the contents they’re seeing as well as how inconsistent the UI elements itself; judging from the unruly layout. With these peculiarities present, this proves that Explorer.ID mobile application hasn’t met the usability standard criteria. To resolve this problem, the author evaluate the mobile application thoroughly with heuristic usability criteria to find the main root of the problems and eliminate them completely for smooth running mobile application. This method is deemed trustworthy for new mobile applications development because this method generates criteria that corresponds with Jacob Nielsen’s Usability principles. Previous research analysis will also be implemented to build appropriate visual communication strategies when designing the UI/UX of Explorer.ID mobile application, such as choosing the right voice and tone for the micro copy to choosing the suitable font that best represent the users demographic and Explorer.ID’s own brand personality.